Production and utilization of pyochelin by clinical isolates of Pseudomonas cepacia. - Sokol, P A (1986)
Forty-three Pseudomonas cepacia isolates were screened for the production of pyochelin. Twenty-one (49%) produced pyochelin, and 22 (51%) were pyochelin negative. Of the 21 strains producing pyochelin, 18 were from patients with severe infections, 11 of which resulted in death. Of the 22 strains which did not produce pyochelin, 13 were from patients with mild or moderate infections. Pyochelin production by P. cepacia isolates infecting cystic fibrosis patients correlates with morbidity and mortality in these patients. Pyochelin was shown to stimulate the in vitro growth of P. cepacia in the presence of transferrin. P. cepacia isolates were able to accumulate 59Fe-pyochelin regardless of whether they produced this siderophore.